AS PERCEPÇÕES DOS PROFESSORES ACERCA DA RELAÇÃO COM O SABER DOS ESTUDANTES NA CONSTRUÇÃO DOS CURRÍCULOS ESCOLARES NO INSTITUTO FEDERAL DO PARANÁ – CÂMPUS DE IRATI - PRADO, PABLO JONATHAN (2022)
The scholar environment is very diverse and complex, where there exists a great number of agents like students and teachers. Each one belongs to a certain context of origin that helps them in the construction of their world visions, values and relations with the school. In that regard, many cultures exist and then a series of codes that are learned from the contexts and incorporated by the subjects in their life contexts. In the middle of that, the teachers are developing their work and doing the construction of the scholar curriculum, the real and the documental. This study delimits its research problem from the search to accomplish a first intersection between Bernard Charlot and Basil Bernstein's theories. The main goal of the investigation is to understand how the relationship with the knowledge of the students of the Federal Institute of Paraná - Campus of Irati influences the curriculum choices of the teacher in the development of their works. In that regard, under the structuralist research conception, using a qualitative research approach and methodological procedures as the semi-structured interviews and the focus group in the development of this research, the goal of this investigation is to debate how the Primary Context from Berstein influences in the relationship of the students, specially how the intersections between Charlot and Bernstein acts in the Pedagogical Discourse Model, mainly in the construction of the instructional discourse in scholar context. Besides that, it was found that the relationship with the knowledge of the IFPR students influences the curricular choices of the teachers. However, things like the structure of the institution are a differential and helps the teachers to apply a curriculum fundamented with more emphasis in instrucionals discourses.